Discourse towards understanding the impacts of humour in foreign language classes - Mustafa, Muhammad; Muhammad, Lubna Ali (Yayasan Mitra Persada Nusantara, 2023)
The phenomenon of humour in every sphere of one's life has a vital role. This project involves the element of humour in EFL classes. The purpose to conduct this research is to investigate how much is the application of humor important, its role, and effectiveness in EFL classes. Mix method/ Qualitative and quantitative types of research have been used for the study. To collect the data, survey forms and questionnaires were used. For data analysis of the collected data, the application namely SPSS was used by the researchers. So the result shows that it is a good technique to apply the mechanism of humour in teaching, especially in foreign language classes.